2011
DOI: 10.5402/2011/847684
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Cervical Cancer

Abstract: Cervical cancer (CC) is the third most common cancer in women worldwide; however, CC is a preventable disease, and much effort should be done to prevent it. Persistence of high-risk HPV infection is the strongest epidemiologic risk factor for CC, however it is not sufficient for development of the disease it cofactors should be present. In 2004; IARC listed cervical cancer among those causally related to smoking. Smoking interferes with incidence and prevalence of HPV infection and is associated with cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 54 publications
2
75
0
3
Order By: Relevance
“…There is a link between the history of smoking or current smoking, with cervical cancer (Fonseca-Moutinho, 2011;Hildesheim et al, 2001;Kim et al, 2012;Plummer et al, 2003). In a large cohort study, the risk of cancer was reduced by 50% among those who stopped smoking for 10 years when compared with those who continued to smoke.…”
Section: Behavioral Factors -Smokingmentioning
confidence: 99%
“…There is a link between the history of smoking or current smoking, with cervical cancer (Fonseca-Moutinho, 2011;Hildesheim et al, 2001;Kim et al, 2012;Plummer et al, 2003). In a large cohort study, the risk of cancer was reduced by 50% among those who stopped smoking for 10 years when compared with those who continued to smoke.…”
Section: Behavioral Factors -Smokingmentioning
confidence: 99%
“…All meta-analyses and multicentric reports highlight that smoking is an important environmental carcinogenic cofactor for cervical neoplasia (36)(37)(38)(39). A study taking into account 150 smoking women diagnosed with cervical neoplasia showed significant association with an increased risk of 4.19-folds of developing cervical cancer in association of GSTM1 null genotypes (40).…”
Section: Discussionmentioning
confidence: 99%
“…In the proliferative phase, the blood vessels will undergo angiogenic process through a formation of spiral arterioles. VEGF and its receptors (VEGFR-1 and VEGFR-2), fibroblast growth factor-2 (FGF-2) and its receptor (FGFR-1 and FGFR-2), epidermal growth factor (EGF) and its receptor EGFR are known to be essential components in the angiogenic process and function of blood vessels in endometrium 7,27 .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a potential growth factor required in the process of endometrial proliferation, as well as plays a role in inducing increased permeability and angiogenesis in endometrial spiral arterioles 6 . In uterine cervix, smoking involved in the process of metaplasia and proliferation of uterine cervix cells 7 .…”
Section: Introductionmentioning
confidence: 99%